ANALYSIS OF HEALTH POLICY IN INDONESIA FOLLOWING THE PASSAGE OF THE OMNIBUS LAW ON INDONESIAN HEALTH LEGISLATION OF 2023 - Syaipudin, Syaipudin (Department of Government, FISIP, Universitas Padjadjaran, 2026)
This study analyzes Indonesia’s health policy reform following the enactment of Law No. 17 of 2023 on Health, which adopts an omnibus law approach to consolidate fragmented health regulations. Previous studies have discussed the legal and institutional dimensions of the Health Law, but have given limited attention to how the law reshapes health governance and to the challenges that emerge during its early implementation. This study employs a qualitative, document-based policy analysis, examining Law No. 17 of 2023, academic drafts, government publications, policy reports, scholarly articles, and stakeholder responses from professional associations and civil society. The findings show that the Health Law seeks to harmonize overlapping regulations, strengthen health workforce governance, and improve access to health services. Its implementation faces several challenges, including limited public participation during the policy-making process, tensions with professional organizations, uneven regional health capacity, and uncertainty regarding derivative regulations. The study argues that the effectiveness of the Health Law depends not only on regulatory simplification but also on inclusive governance, transparent implementation, and continuous policy evaluation. These findings contribute to debates on health policy reform in Indonesia by highlighting the gap between regulatory ambition and implementation readiness.